Evaluating the efficacy and acceptability of vagus nerve stimulation for fibromyalgia: a PRISMA-compliant protocol for a systematic review and meta-analysis - Cai, Yunhuo; Zhang, Yajun; Fang, Yiyan; Hu, Hantong; Li, Xingling; Fang, Lianqiang (Frontiers in Neurology, 2024)
Background Fibromyalgia has imposed substantial burdens on patients’ health and well-being, yet effective therapeutic options for this condition remain limited. Recently, vagus nerve stimulation (VNS) has emerged as a promising therapy for fibromyalgia. Nonetheless, despite the increasing number of randomized clinical trials (RCTs), current evidence remains inconclusive. Therefore, this protocol of a systematic review and meta-analysis aims to synthesize the existing evidence to clarify the efficacy and acceptability of VNS for treating fibromyalgia. Methods A comprehensive search for eligible RCTs will be conducted across nine bibliographic databases, namely PubMed, Cochrane Library, Embase, AMED, PsycINFO, PEDro, Chinese BioMedical Literature Database, Chinese National Knowledge Infrastructure, and Wangfang database. Data obtained from the included studies will be synthesized quantitively using RevMan 5.4.1 for meta-analyses. The methodological soundness of included RCTs will be assessed via the Cochrane’s updated risk of bias tool (version 2.0). Additionally, sensitivity analyses, publication bias assessment, and subgroup analyses will be conducted as appropriate. Finally, we will utilize the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system to evaluate the certainty for the body of evidence. Conclusion The findings of our study are anticipated to ascertain the efficacy and acceptability of VNS as a promising treatment option for fibromyalgia. This will not only fill current research gap but also identify potential areas for future research. The findings will provide essential guidance for evidence-based treatment decisions for fibromyalgia, benefiting both patients and clinicians.